2011
DOI: 10.1007/s12529-011-9175-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pain Controllability and Discrepancy in Social Support on Depressed Mood Among Patients with Chronic Pain

Abstract: Findings suggest the relative importance of discrepancy in emotional support from a significant other, especially for patients with low pain controllability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
3
17
0
4
Order By: Relevance
“…This result is congruent with evidence that shows that in stressful situations the emotional and instrumental support of a confidant is associated with lower negative affect and a reduction of the organism's psychobiological reaction to stress. 34,35 Furthermore, this result is in line with evidence showing reduced physical, functional and emotional well-being in isolated women with breast cancer. 7 Depression is the psychosocial variable most strongly associated with the QOL facets of general health and social function.…”
Section: Discussionsupporting
confidence: 88%
“…This result is congruent with evidence that shows that in stressful situations the emotional and instrumental support of a confidant is associated with lower negative affect and a reduction of the organism's psychobiological reaction to stress. 34,35 Furthermore, this result is in line with evidence showing reduced physical, functional and emotional well-being in isolated women with breast cancer. 7 Depression is the psychosocial variable most strongly associated with the QOL facets of general health and social function.…”
Section: Discussionsupporting
confidence: 88%
“…This finding has been echoed in other studies that emphasize marriage as an important source of social support, and in some instances, the preferred source of support (Cho, Zunin, Chao, Heiby, & McKoy, 2012). Spouses are likely to share similar values, characteristics and experiences with each other that are important elements of effective social support (Thoits, 1986).…”
Section: Discussionsupporting
confidence: 55%
“…This finding is partially supported by Cho et al (2012) who found that patients with chronic pain preferred receiving emotional/affectionate types of support to tangible support. High tangible support can have negative outcomes by causing people feel to helpless or burdensome to others.…”
Section: Discussionmentioning
confidence: 67%
“…The inverse relationship between social support and depression is well established [27]. Social support may be particularly important in the context of severe or uncontrollable pain [28, 29]. There is some evidence that those who have a hard time controlling their pain receive less social support than they desire, which contributes to depression [28].…”
Section: Discussionmentioning
confidence: 99%